PEMBELAJARAN BAHASA ARAB BERBASIS MULTIPLE INTELEGENCY - SAID, MOCH.; MUNIR, MUHAMMAD MUBASYSYIR (Prodi Pendidikan Bahasa Arab Fakultas Agama Islam, 2022)
The perception of intelligence in our time has changed a lot in recent times, with Gardner’s multiple intelligence theory showing that intelligence includes nine intelligences: linguistic intelligence, logical - mathematical intelligence, interpersonal intelligence, intrapersonal intelligence, bodily - kinesthetic intelligence, musical intelligence, spatial intelligence, naturalist intelligence and existential intelligence. This theory has changed the pedagogical perception of teachers towards their students, as a smart student is not only the one who solves the mathematical questions, but each individual has his or her own intelligence, and may differ from each other. This phenomenon helps to choose the appropriate method or means of education for students given the type of intelligence they have.